Crítica de la libertad sindical - Ermida Uriarte, Oscar (2012)
Critique of trade union freedomThe article begins of the protective character of Labor Law and of the study of trade union freedom as an instrument of compensatory inequality, to analyze critically the protection of this right in the Committeeof Trade Union Freedom. Then, it develops causes of the current crisis of trade unionism and the possibility of atrade union self-reform and of an International Court of Trade Union Freedom. Finally, the article presents some strategies for overcoming the crisis of trade unionism